Pregled dosežkov madžarske slovenistike po letu 1990 - Várkonyi, Alma (Slavia Centralis, 2020)
The Achievements of the Slovene Studies in Hungary from 1990 until now – an OverviewIn the last 20 years, the research of Sloveno-Hungarian literary, linguistic and cultural connections has been very fruitful. The following paper aims to presents the most important publications related to the Slovene culture issued after 1990, including but not limited to the scientific publications on Slovene Studies (including the papers on Literary History, Linguistics, History and History of Culture), the literary and scientific publications of the Hungarian Slovene minority and the Hungarian translations of the Slovene literature.
Keywords: Slovene Studies; Sloveno-Hungarian literary and linguistic connections; Slovenes in Hungary; history; lexicography; artistic translation